The effect of financial performance on directors remuneration / Siti Marliah Buhari - Buhari, Siti Marliah (Faculty of Business and Management, 1995)
There is a growing controversy in many countries that the top management remuneration is totally out of tune with the firms performance. However , some economic theories of efficient compensation and remuneration predict a positive relationship between management pay and firm performance. The study try to determine whether these economic theories are acceptable in the Malaysian labour market. Data from the sample of 12 commercial banks from 1984 to 1993 is examined, using the average of EPS, EBIT, EAT and Dividend payable with the average remuneration receive by its directors. The remuneration is regressed against the EPS, EBIT, EAT and Dividend payable using Least Square method on a Single Linear Function. The empirical study shows that each of the variable used namely, EPS, EBIT, EAT and Dividend payable proposed a positive relationship. Referring to the test conducted, T- statistics, F-test and R2 indicates that this relationship is statistically significant except for the F - test of the EPS is insignificant Therefore, it is concluded that the financial performance do effect its directors' remuneration and theories of efficient compensation and remuneration saying that there is a positive relationship between management pay and financial performance is applicable in Malaysian labour market.